Theme of oMarriage with a Foreignero: Nationalism and Female Authorship in the Early Republican Novel - Ural, Tuelin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2009)
Two novels written by female authors, Sinekli Bakkal and Bahar Cicei, claim that while the new Turkish nation adopted a Western lifestyle, its original character was built upon its female members' effort to protect its essence. Female authorship seems to be dominated by nationalism. However, a female voice can still be heard in the characterization of female protagonists as strong personalities. Thus, the authors of these works should be judged as writers who try to express themselves as women under a dominant ideology.
Keywords: Area Studies